Systematic Review: Pengendalian Tembakau dan Penyakit Arteri Koroner - Santoso, Audia Fijratullah; Farida, Bunga; Ninda, Gina Fitri; Hibatullah, Faiz Nur; Sari, Nur Mufida Wulan; Saleem, Haitam Thaleb; Martini, Santi; Mahmudiono, Trias (Universitas Airlangga, 2024)
Backgrounds: The prevalence of cigarette consumption in Indonesia has reached a level that is cause for concern. Currently, more than one-third (36.3%) of Indonesia's population is classified as smokers. The World Health Organization (WHO) ranks Indonesia as the third-largest cigarette market in the world, after China and India. In fact, the prevalence of adult male smoking in Indonesia is the highest (68.8%) in the world, so tobacco consumption has many negative impacts on health, one of which is the main cause of non-communicable diseases (NCDs), such as coronary artery disease (CAD). Tobacco control is one of the efforts that can be made to prevent non-communicable diseases, namely coronary heart disease. Coronary artery disease is a pathological condition that arises due to the accumulation of atheroma in the blood vessels that supply blood to the heart, causing narrowing of the coronary arteries. Objectives: The aim of this study is to identifying tobacco as the main cause of non-communicable diseases such as coronary artery disease and tobacco control policies Methods: The method of this study is a literature review using PRISMA as a guide. Articles obtained from databases such as PubMed and Google Scholar with specific relevant keywords “tobacco AND coronary artery disease”, “tobacco AND Non-communicable disease”, “tobacco control”, and “tobacco policy”. Article restricted to only original study within 2019 until 2023. Results: Tobacco control and prevention efforts that can be carried out regarding NCDs according to the 30 articles are controlling media by a massive pictorial warning; prohibition advertising, promotion, and sponsorship; controlling the price of tobacco by increasing the excise, tax, and selling price; restriction on smoking area, and smoking cessation therapy in a health facility that covered by insurance. Nicotine replacement therapy could be the choice for smoking cessation in CAD patients. Conclusions: Since limited research on smoking cessation therapy, especially in patients with CAD, it is necessary to develop various therapeutic methods that are easier, affordable, and safe.